Performance Evaluation and Portfolio Optimization in Emerging European Stock Markets: Evidence from Hungary and Romania - Kulcsár, Edina; Veres, Edit; Fogarasi, József (Public Finance Quarterly, 2025)
The objective of this study is to conduct a comparative risk and performance analysis of two leading stock indices from Central and Eastern Europe: Hungary's BUX and Romania's BET. Specifically, the research addresses whether applying different risk and performance measures affects the assessment of investment attractiveness and examines how altering stock weights within portfolios can optimise returns and risk. Given increasing global financial uncertainties and the distinct characteristics of emerging markets, the research holds significant scientific and practical relevance for investors and policymakers alike. The analysis employed daily closing prices of BUX and BET indices, along with their component stocks' weights, spanning from December 2022 to June 2023. Advanced statistical methods, including traditional performance ratios (Sharpe, Treynor, Jensen) and advanced risk measures (VaR, CVaR, semivariance), were implemented using R statistical software for robust portfolio optimisation. Results indicate that Hungarian portfolios exhibit higher overall risk, while Romanian portfolios present better diversification and closer alignment with normal distribution characteristics. Portfolio optimisation revealed that strategic weight adjustments significantly enhance portfolio performance, demonstrating the effectiveness of modern statistical methods in portfolio management for emerging markets.